Early-onset and recurrent reflex syncope is associated with left ventricular diastolic filling and left atrial function properties. (25th November 2020) - Roumelis, P; Antoniadis, A; Sotiriadou, M; Pagkourelias, E; Konstantinidis, P; Meletidou, M; Bakogiannis, C; Toumpourleka, M; Mpoulmpou, A; Kyriakou, P; Papadopoulos, C; Fragakis, N; et al.
Abstract: Background/Introduction: The effects of the left atrial and ventricular function in the pathophysiology of reflex syncope remain elusive. Head-up tilt table test (HUTT) is frequently used in the diagnostic workup of patients with syncope, but the outcomes of HUTT have not been attributed to any anatomical or functional cardiac characteristics. Purpose: We sought to assess the effects of anatomical and functional echocardiographic features of the left atrium and the left ventricle at rest in the clinical presentation of syncope and the outcomes of HUTT. Methods: We investigated patients with a history of syncope and symptoms suggestive of reflex syncope who underwent HUTT. Specific echocardiographic indices of left cardiac morphology and function were assessed at rest. The patients were divided into two groups, those who presented with syncopal episodes at age <35 years (group A) and those who presented with syncopal episodes at age >35 years (group B). Results: In 119 patients (age 46.75±21.17 years, 69 women), patients in group A exhibited a higher chance for numerous (>3) syncopal episodes (odds ratio [OR] 3.4, 95% Confidence Interval [CI] 1.41 to 7.93, p<0.05). Group A showed also a trend for positive HUTT (OR 1.99, 95% CI 0.97 to 4.23, p=0.08). In patients with positive HUTT, Group A had higher E-wave velocity (0.83 vs 0.65 m/sec, p<0.05), lower A-wave velocity (0.60 vs 0.75 m/sec, p<0.05), higher E/A ratio (1.54 vs 1.00, p<0.05), higher e' wave velocity (0.16 vs 0.10 m/sec, p<0.05) and lower E/e' (5.64 vs 7.85, p<0.05). Also, patients in group A exhibited lower left atrial volumes (min 9.88 vs 16.21 ml, p<0.05, max 30.42 vs 44.89 ml, p<0.05), higher left atrial strain reservoir (40.56 vs 32.42%, p<0.05) and higher left atrial strain booster (25.94 vs 18.06%, p<0.05). Conclusion(s): Patients with a younger age of onset and recurrent syncopal episodes manifest smaller dimensions of the left atrium with distinct patterns of diastolic performance and better reservoir and booster function. These findings may indicate a more pronounced susceptibility of this group of patients to preload reduction, thereby triggering the mechanism of reflex syncope. Funding Acknowledgement: Type of funding source: None